Backed‐Up, Saturated, and Stagnant: Effect of Milldams on Upstream Riparian Groundwater Hydrologic and Mixing Regimes. Issue 10 (3rd October 2022) - Sherman, Melissa; Hripto, Johanna; Peck, Erin K.; Gold, Arthur J.; Peipoch, Marc; Imhoff, Paul; Inamdar, Shreeram
Abstract: How milldams alter riparian hydrologic and groundwater mixing regimes is not well understood. Understanding the effects of milldams and their legacies on riparian hydrology is key to assessing riparian pollution buffering potential and for making appropriate watershed management decisions. We examined the spatiotemporal effects of milldams on groundwater gradients, flow directions, and mixing regime for two dammed sites on Chiques Creek, Pennsylvania (2.4 m tall milldam), and Christina River, Delaware (4 m tall dam), USA. Riparian groundwater levels were recorded every 30 min for multiple wells and transects. Groundwater mixing regime was characterized using 30‐min specific conductance data and selected chemical tracers measured monthly for about 2 years. Three distinct regimes were identified for riparian groundwaters—wet, dry, and storm. Riparian groundwater gradients above the dam were low but were typically from the riparian zone to the stream. These flow directions were reversed (stream to riparian) during dry periods due to riparian evapotranspiration losses and during peak stream flows. Longitudinal (parallel to the stream) riparian flow gradients and directions also varied across the hydrologic regimes. Groundwater mixing varied spatially and temporally between storms and seasons. Near‐stream groundwater was poorly flushed or mixed during storms whereas that in the adjacent swales revealed greater mixing. This differential groundwater behavior was attributed to milldam legacies that include: berm and swale topography that influenced the routing of surface waters, varying riparian legacy sediment depths and hydraulic conductivities, evapotranspiration losses from riparian vegetation, and runoff input from adjoining roads. Plain Language Summary: Riparian zones can buffer streams from upland nitrogen pollution and are thus considered as important water quality management practices. How the presence of milldams affects groundwater flow paths and their buffering capacity is not known. This study showed that milldams back up stream water above dams, reduce the groundwater gradients from the upland to the stream, and also result in their reversal during summer dry conditions and floods. Milldams reduced the mixing of groundwaters for near‐stream sediments. This response was attributed to the topographic and sediment conditions associated with the milldams. Key Points: Milldams raise riparian groundwater levels, decrease hydraulic gradients, and cause reversals in groundwater flow Milldam legacies contribute to reduced groundwater mixing in near‐stream sediments Altered groundwater regimes due to milldams could affect riparian water quality processes